1998
DOI: 10.1590/s0066-782x1998000200009
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcemia complicada por miocardite

Abstract: Meningococcemia Complicated by Myocarditis We report a case of a 26-year old man with meningococcemia complicated with myocarditis (ventricular dysfunction and myocardial ischemia), that required treatment for heart failure. Regression of myocardial dysfunction was observed six months after the infection. Homem de 26 anos com meningococcemia (meningite), complicada por miocardite (disfunção ventricular e isquemia miocárdica), requereu tratamento para insuficiência cardíaca e evolui com regressão da disfunção m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Previous evidence has shown that resolution of clinical myocarditis is often prolonged and incomplete 14. However, this report reaffirms the possibility of rapid resolution of severe meningococcal myocarditis, which has been seen before 6.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous evidence has shown that resolution of clinical myocarditis is often prolonged and incomplete 14. However, this report reaffirms the possibility of rapid resolution of severe meningococcal myocarditis, which has been seen before 6.…”
Section: Discussionsupporting
confidence: 81%
“…This complication is not recognized very frequently, but has been described before 6,11–14. An autopsy study in children revealed the presence of myocarditis in 42% of 31 children who had died of meningococcal infection, though the extent of inflammation was mild in the majority,15 which suggests that myocarditis may be more common than is recognized clinically.…”
Section: Discussionmentioning
confidence: 95%
“…The unusual thing about our patient was her rapid and successful recovery within a span of a few days. Previous evidence has shown that resolution of clinical myocarditis is often prolonged and incomplete [ 9 ]. However, this report reaffirms the possibility of rapid resolution of severe meningococcal myocarditis, which has been seen before [ 10 ].…”
Section: Discussionmentioning
confidence: 99%